1997
DOI: 10.1128/mcb.17.10.5856
|View full text |Cite
|
Sign up to set email alerts
|

CpG Islands from the α-Globin Gene Cluster Increase Gene Expression in an Integration-Dependent Manner

Abstract: In contrast to other globin genes, the human and rabbit ␣-globin genes are expressed in transfected erythroid and nonerythroid cells in the absence of an enhancer. This enhancer-independent expression of the ␣-globin gene requires extensive sequences not only from the 5 flanking sequence but also from the intragenic region. However, the features of these internal sequences that are responsible for their positive effect are unclear. We tested several possible determinants of this activity. One possibility is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…This suggested that the effects of the CpG island outside the proximal promoter were to provide a more permissive environment for promoter activity than do bulk A+T-rich DNAs, but that this effect is not dependent on binding of specific transactivators at discrete locations. The postulated general effect of CpG islands is supported by three lines of evidence: (1) The level of gene expression increases with increasing size of the CpG island included in transfection constructs; (2) deletion of prominent binding sites for Sp1 and YY1 has no effect; and (3) addition of ␣-globin gene promoter fragments to a transcriptionally inactive CpG island gives a much higher level of expression after integration into the genome than does addition of these fragments to an A+T-rich DNA fragment (Shewchuk and Hardison 1997). This more permissive effect of CpG islands may be exerted at least in part at the level of chromatin structure, as CpG island DNA from the ␣-globin gene has a much lower affinity for nucleosome reconstitution in vitro than does the A+T-rich DNA fragments from the ␤-globin gene .…”
Section: Loci With Functional Tests Based On Sequence Alignmentsmentioning
confidence: 97%
“…This suggested that the effects of the CpG island outside the proximal promoter were to provide a more permissive environment for promoter activity than do bulk A+T-rich DNAs, but that this effect is not dependent on binding of specific transactivators at discrete locations. The postulated general effect of CpG islands is supported by three lines of evidence: (1) The level of gene expression increases with increasing size of the CpG island included in transfection constructs; (2) deletion of prominent binding sites for Sp1 and YY1 has no effect; and (3) addition of ␣-globin gene promoter fragments to a transcriptionally inactive CpG island gives a much higher level of expression after integration into the genome than does addition of these fragments to an A+T-rich DNA fragment (Shewchuk and Hardison 1997). This more permissive effect of CpG islands may be exerted at least in part at the level of chromatin structure, as CpG island DNA from the ␣-globin gene has a much lower affinity for nucleosome reconstitution in vitro than does the A+T-rich DNA fragments from the ␤-globin gene .…”
Section: Loci With Functional Tests Based On Sequence Alignmentsmentioning
confidence: 97%
“…This inhibition is modulated by transcriptional termination signals located between the two α genes. Recently, Shewchuk and Hardison (1997) have shown that the size of CpG islands in the α-globin gene cluster, which includes both 5' flanking and intragenic regions, positively correlates with the level of gene expression, also suggesting that a mechanism at the chromatin structure level may be involved.…”
Section: A) Allele Polymorphismmentioning
confidence: 99%
“…Stably transfected cells carry the test plasmids integrated into a chromosome and hence the template DNA is in a normal chromatin structure. Different kinds of questions can be addressed with the two types of transfections; e.g., transient transfections can provide a rapid means for identifying promoters and enhancers (2) whereas stably transfected cells can reveal position effects (21,22) or integration-dependent enhancement (14,16).…”
Section: Introductionmentioning
confidence: 99%